United by Context, Divided by Collection: The Nineteenth Century Collecting of Prehistoric Artifacts from Villafrati (Sicily, Italy) .......... 179 - D’Amico, Serena (Collecting Antiquities from the Middle Ages to the End of the Nineteenth Century: Proceedings of the International Conference Held on March 25-26, 2021 at the Wrocław University Institute of Art History, 2021)
In the historical framework of the newly unified Italy (1861), in parallel with the collection of the classical age materials, paleoethnological collections came to be defined following different dynamics of formation. Compared to the former, which traditionally occupied the field of the humanities, prehistoric artefacts struggled to be included among the sciences of antiquity, finding their place among the natural sciences instead. Particularly, natural caves proved to be exceptional archaeological contexts offering much more scientific data than the open-air sites about the definition of the most ancient history of Man and, for this reason, privileged places for the recovery of artifacts. The article aims to present the collecting history of the prehistoric materials coming from the caves of Mount Chiarastella, whose collection and formation practices fit into the framework of the Sicilian collecting history of the second half of the 19th century. Many actors were involved as well as purposes for the recovery of the artifacts, a fact that has led to an inevitable consequence, the dispersion of the artifacts in three public museums and the loss of their traces among private collections. Nevertheless, the multidisciplinary approach adopted in the research has made it possible to overcome the problems linked mainly to the lack of documentary sources, allowing the reconstruction of the entire history of research on the site, as well as the first faithful reading of the original archaeological context.